1984
DOI: 10.1002/jso.2930250415
|View full text |Cite
|
Sign up to set email alerts
|

Successful immunotherapy in a murine metastasizing fibrosarcoma model

Abstract: Antigenic differences were demonstrated between the primary murine fibrosarcoma and its metastases. Immunization with irradiated primary tumor cells (TC) protected C57B1/6J mice against subsequent challenge with those cells, but not against challenge with cells from pulmonary metastases (PMC). Mice immunized with irradiated PMC were protected from challenge with those cells, but not against challenge with TC. Mice with fibrosarcomas produced by the injection of 5 X 10(3) cells from the primary tumor were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…We have shown previously that immunotherapy with live tumor cells is effective in a model of minimal residual tumor bearing syngeneic mice [1,2,5,14]. The results indicated that therapy with live tumor cells improved the survival rate significantly, and was even more effective when tumor cells from metastatic sites (lung or liver) were combined with primary tumor cells.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…We have shown previously that immunotherapy with live tumor cells is effective in a model of minimal residual tumor bearing syngeneic mice [1,2,5,14]. The results indicated that therapy with live tumor cells improved the survival rate significantly, and was even more effective when tumor cells from metastatic sites (lung or liver) were combined with primary tumor cells.…”
Section: Introductionmentioning
confidence: 64%
“…The tumor grows progressively at the injected site and metastasizes spontaneously to liver or lung or both. Mice succumb within 30 days if untreated [2].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations